Pathognomonic features and ultrastructural of Koi Herpesvirus infected Oreochromis niloticus - BUDI RIANTO WAHIDI; UUN YANUHAR; MOHAMAD MOHAMAD FADJAR; SRI ANDAYANI (Society for Indonesian Biodiversity, 2019)
Abstract. Wahidi BR, Yanuhar U, Fadjar M, Andayani A. 2019. Pathognomonic features and ultrastructural of Koi Herpesvirus infected Oreochromis niloticus. Biodiversitas 20: 497-503. Koi Herpesvirus (KHV) has caused considerable losses in the cultivation of the Cyprinidae family worldwide. In addition to infecting Cyprinidae, KHV can also infect other freshwater fish. This study reports histopathology and ultrastructural analysis of KHV that infect Nile tilapia. Although there are no specific clinical symptoms, pathognomonic indicating Nile tilapia fish has been infected with KHV have been found, i.e. through the formation of intranuclear inclusion body and cell swelling which essentially experience chromatin margination. In addition, histopathology results indicate changes or damage to other tilapia tissue, i.e. necrosis, hypertrophy, edema, hemorrhage, inflammation, congestion, degeneration, and apoptosis. These results indicate that KHV has been distributed and replicated in tilapia organs. Based on the Transmission Electron Microscopy (TEM) analysis, KHV virions have been detected in the cytoplasm or outside the cells on a size of 150-170 nm.